(3hajGJ GdCYjGf hCfHGA CHfGA GdReGfs - (3GHf NdcGf , CMeO Hf eMeO Hf EHQGgje Hf CHj HcQ GdHQecj GdGQHdj, TeS GdOjf CHh GdYHGS,J (B681 (3g` s ((3YHO GdQMef Hf CMeO Hf Ydi Hf GdMSjf Hf jhSa GdMdHi s)
(3ChdgG (B:s
(3jHOC HJQLeI GdEeGe Ydi Hf GdMSjf Rjf GdYGHOjf s
(3GdfSNI HgG MhGTs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B220 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B59s
Keywords: (3GdJGQjNs